2012
DOI: 10.3342/ceo.2012.5.s1.s6
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evoked Potentials under Active and Passive Hearing Conditions in Adult Cochlear Implant Users

Abstract: ObjectivesSpeech perception abilities, which vary widely among cochlear implant (CI) users, are considered to be associated with the integrity of the central auditory pathways from the auditory nerve to the cortex. Therefore, auditory evoked potentials (AEPs) are used to evaluate central auditory processing, which is thought to contribute to speech perception in CI subjects. In AEPs, the P300 component reflects the cognitive ability of subjects to detect and respond to stimuli and has most frequently been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 6 publications
3
22
0
Order By: Relevance
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) contrast with different places of articulation (Groenen et al, 2001;Henkin et al, 2009), likely showing similar results to the studies using a difficult tone contrast (Roman et al, 2005;Obuchi et al, 2012), but not those using an easy contrast (Zhang et al, 2011).…”
Section: Erp Results In the Quiet Conditionmentioning
confidence: 48%
“…(For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) contrast with different places of articulation (Groenen et al, 2001;Henkin et al, 2009), likely showing similar results to the studies using a difficult tone contrast (Roman et al, 2005;Obuchi et al, 2012), but not those using an easy contrast (Zhang et al, 2011).…”
Section: Erp Results In the Quiet Conditionmentioning
confidence: 48%
“…Generally, implanted post verbal adult patients showed longer latencies compared to hearing patients with the same age [12]- [15].…”
Section: Introductionmentioning
confidence: 84%
“…9 Furthermore, Hahne et al and Obuchi et al also reported delayed latencies and smaller amplitudes in CI patients than in normal hearing controls. 10,11 This finding may be related to difficulties faced by CI subjects in using temporal and spectral cues. They appeared to require longer time to process the incoming information as compared to the normal hearing subjects.…”
Section: Discussionmentioning
confidence: 95%